The importance of colorectal cancer secondary prevention - Cieśla, Paulina; Cieśla, Beata; Cieślak, Halina (Nursing Problems / Problemy Pielęgniarstwa, 2008)
In Poland colorectal cancer is the second on the list according to the incidence rate and the third according to the mortality rate among all kind of malignant tumor developed in females and males. About 45% of colorectal cancer is located in rectum and about 30% in sigmoid colon. The morbidity is more frequent along with the patient’s age, but diagnosed early enough is in 90% curable. Unfortunately, in Poland, the colorectal cancer is still in half of cases diagnosed too late. To improve the situation the best weapon are regular screening methods concentrated on colorectal cancer: occult blond test, endoscopic examination, double contrast enema as well new methods like virtual colonoscopy.